Reflection of food culture in the phraseological unit of the chinese language (Journal of Oriental Studies, 2016)
In this article author made the analysis of reflection of food culture in the Chinese language, especially in the phraseological unit ofthe Chinese language, which consists the big part of very rich Chinese culture.